Advice to a young scientist - Sercan Tırnavalı (Türk Kütüphaneciliği)
Nobelist British Biologist Sir Peter Brian Medawar passed of years with the accumulation of his scientific research which consists of young people who want to enter the world of science to service offers with his book. The qualifications required to become a scientist, conditions and scientific research methods are discussed with examples and advice to young people in the book.